Pronoun Production Order in a Gender-Neutral Language: A Single Case Study of a Typically Developing Indonesian Child - Jap, Bernard A.J (Paradigma: Jurnal Kajian Budaya, 2013)
Research in children with normal language development has shown that there is a certain order in the production and learning of pronominal forms. To one’s knowledge, there has yet to be a study on the pronoun development of Indonesian speaking children whose native language do not distinguish between the nominative-accusative form (e.g. in English, I/me – Indonesian, saya/saya) and at the same time being gender neutral (e.g. in English, he/she – Indonesian, dia/dia). The present study follows the personal pronoun development of a (Jakarta) Indonesian-speaking child from 24 months to 46 months of age.